Relevance of Fair Value Disclosures in Spanish Credit Institutions - David Delgado-Vaquero; José Morales-Díaz; Miguel A. Villacorta (Revista de Contabilidad: Spanish Accounting Review, 2022)
Spanish quoted credit institutions have applied IFRS for their consolidated financial statements since 2005. IFRS implied the implementation of the fair value measurement model for a greater number of financial instruments than previously, as well as the disclosure of the difference between fair value and book value for those financial instruments not measured at fair value on the balance sheet.